Di-tert-butylbis(N-isopropyl-N-methyldithiocarbamato-kappa S-2,S `)tin(IV) - Muthalib, A.F.; Baba, I.; Samsudin, M.W.; Ng, S.W. (International Union of Crystallography, 2010)
The dithiocarbamate anions in the title compound, [Sn(C4H9)(2)(C5H10NS2)(2)], chelate to the Sn-IV atom, which is six- coordinated in a skew- trapezoidal- bipyramidal geometry. The molecule lies across a twofold rotation axis. The crystal studied was a non- merohedral twin, the ratio of the twin components being 0.82 (1): 0.18 (1).